Biogenic synthesis of gold nanoparticles from Halymenia dilatata for pharmaceutical applications: Antioxidant, anti-cancer and antibacterial activities. (October 2019) - Vinosha, Manoharan; Palanisamy, Subramanian; Muthukrishnan, Ramasamy; Selvam, Samayanan; Kannapiran, Ethiraj; You, SangGuan; Prabhu, Narayanasamy Marimuthu
Graphical abstract: Highlights: Biogenic synthesis of gold nanoparticles using the aqueous extract of H.dilatata The synthesized Hd-AuNPs were confirmed by spectral and microscopic examination. Antioxidant, Anti-cancer and Antibacterial properties of Hd-AuNPs were studied. First report on the biological activities of GNPs synthesized from H. dilatata . Abstract: Biogenic synthesis of metal nanoparticles using seaweeds is more biocompatible and more valuable for biomedical applications. In this study, gold nanoparticles were synthesized from the aqueous extract of Halymenia dilatata (Hd-AuNPs) and characterized by various spectral and microscopic techniques. The Hd-AuNPs exhibit a surface plasmon resonance peak at 529 nm. FT-IR results confirm the presence of polysaccharides and pigments in the extract, which reduce Au 3+ to Au 0 . Microscopic analysis confirmed that Hd-AuNPs were triangular and spherical in shape with an average size of 16 nm. In terms of potential antioxidant properties, DPPH radical scavenging (13.7 ± 0.40 to 58.7 ± 0.85%), reducing power (16.3 ± 0.63 to 62.4 ± 0.60%) and total antioxidant (12.4 ± 0.50 to 56.6 ± 0.74%) activities were reasonably high in Hd-AuNPs compared with the extract alone. In the cytotoxicity assay, the IC50 of Hd-AuNPs was 22.62 μg/ml against HT-29 cancer cells. Similarly, in the antibacterial assay, the highest zone of inhibition (21 mm) was recorded at 100 μg/ml against Aeromonas hydrophila and the activity was proportionate to the concentration of Hd-AuNPs. In addition, the biosynthesis of Hd-AuNPs was non-toxic to zebrafish embryo. Overall, synthesized Hd-AuNPs exhibit commendable antioxidant, anti-cancer and antibacterial activities.